(untitled) (Vietnam Journal of Community Medicine, 2022)
A descriptive cross-sectional study on 424 students to assess the knowledge and practice of oral care and some factors related to dental caries of students at 2 secondary schools Ky Ba and Phu Xuan, Thaibinh city. Research results show that: Female students (64.8%) have a higher risk of tooth decay than male students (35.2%) with p < 0.05 (OR=2.35; 95%CI: 1.55-3.56). There is a difference in tooth decay in urban and rural areas: students at Phu Xuan school have a higher rate of tooth decay than students at Ky Ba school (46.6%; 25.7%; p<0). ,05). Using toothpicks was associated with a higher risk of tooth decay (OR=1.71, 95%CI: 1.12-3.24). Students who did not brush their teeth daily had a higher risk of tooth decay than students who brushed their teeth daily (OR=9.23, 95%CI: 2.19-39.2). Gargling after eating will reduce the risk of malaria (OR=4.18, 95%CI: 2.14-8.15). Students who regularly eat sweets have an increased risk of malaria compared with the group of students who do not regularly eat sweets (OR=2.37, 95%CI: 1.55-3.62). The risk of tooth decay will increase if students do not regularly go for regular dental check-ups (OR=2.02, 95%CI: 1.27-3.23).